A comprehensive comparison between pediatric and adult patients with periodic fever, aphthous stomatitis, pharyngitis, and cervical adenopathy (PFAPA) syndrome. Issue 2 (February 2017) - Rigante, Donato; Vitale, Antonio; Natale, Marco; Lopalco, Giuseppe; Andreozzi, Laura; Frediani, Bruno; D'Errico, Francesca; Iannone, Florenzo; Cantarini, Luca
Abstract Periodic fever, aphthous stomatitis, pharyngitis, and cervical adenopathy (PFAPA) syndrome is a mysterious disorder characterized by periodically recurrent fevers, oropharyngeal inflammation, and adenitis, which mainly affects children, though in very recent times, it has been also recognized in adulthood. We enrolled 115 unrelated pediatric and adult patients with history of periodic fevers who fulfilled the current diagnostic criteria for PFAPA syndrome in three Italian referral centers and highlighted differences between children and adults. Eighty-five children and 30 adults were evaluated: the frequency of flares was significantly higher in pediatric cases, while febrile attack duration was significantly longer in adults. Clockwork periodicity of fever and recurrent pharyngitis were more frequently observed in childhood, but no differences were identified for aphthosis and cervical adenopathy. Conversely, joint symptoms, myalgia, headache, fatigue, ocular signs, and rashes were more common in adults. The simultaneous occurrence of two or three cardinal PFAPA signs did not show any statistical difference between the groups, while the occurrence of only one cardinal manifestation was more frequent in adults. Corticosteroids were effective in 98.82 % of children and 88.2 % of adults. Tonsillectomy was rarely performed, resulting effective in only two patients. Our data illustrate the clinical overlap between pediatric and adult cases of PFAPA syndrome. Adults are characterized by a wider repertoire of inflammatory signs, suggesting that onset in adulthood might leave the disease misdiagnosed. Clinicians, not only pediatricians, should take into account this clinical entity in every patient of whatever age suffering from recurrent fevers of unknown origin.